PERKEMBANGAN TRADISI ZIARAH KUBRO PADA MASYARAKAT KOTA PALEMBANG TAHUN 1970-2008 - Syarifuddin Syukur; Muhammad Irham Fhadillah; Desty Lylyatmi; Supriyanto Supriyanto (Dialogia, 2022)
The Ziarah tradition is one of the traditions of the Indonesian people that is often being held before Ramadan. The great influence of the existence of the Arab communities in the Palembang brought a tradition known to various countries so that it became religious tourism, namely the Ziarah Kubra. Ziarah Kubra  is one of the traditions of the people of Palembang city which is being held every 10 days before Ramadan by visiting the graves of the ulama and leaders of the Palembang Darussalam Sultanate. The purpose of this research is to find out how the emergence of the Ziarah Kubra carried out by the Arab communities in Palembang and to find out how the development of the Ziarah Kubra tradition in the people of Palembang city from 1970-2013. The method used in this research is the historical method. This research has shown that the tradition of the Ziarah Kubra has been brought by the people of Palembang has been developed every year, where's this tradition was only practiced by the Arab communities in the Palembang and relatives of the Palembang Sultanate. Then this tradition began to be open to the public in 1970 and was designated become the religious tourism by the Palembang city government in 2013. So that the people of Palembang continue.